Memory Vulnerability Diagnosis for Binary Program - Tang, Feng-Yi; Feng, Chao; Tang, Chao-Jing (ITM web of conferences, 2016)
Vulnerability diagnosis is important for program security analysis. It is a further step to understand the vulnerability after it is detected, as well as a preparatory step for vulnerability repair or exploitation. This paper mainly analyses the inner theories of major memory vulnerabilities and the threats of them. And then suggests some methods to diagnose several types of memory vulnerabilities for the binary programs, which is a difficult task due to the lack of source code. The diagnosis methods target at buffer overflow, use after free (UAF) and format string vulnerabilities. We carried out some tests on the Linux platform to validate the effectiveness of the diagnosis methods. It is proved that the methods can judge the type of the vulnerability given a binary program.